Prevalence of Blood Types and Alloantibodies of the AB Blood Group System in Non-Pedigree Cats from Northern (Lombardy) and Southern (Sicily) Italy - Eva Spada; Roberta Perego; Luciana Baggiani; Elisabetta Salatino; Vito Priolo; Cyndi Mangano; Maria Grazia Pennisi; Daniela Proverbio (Animals, 2020)
The aims of this study were to determine the prevalence of A, B and AB blood types and alloantibodies in non-pedigree cats from two regions, one in Northern and one in Southern Italy (Lombardy and Sicily, respectively). A total of 448 samples (52.0% from Northern and 48.0% from Southern Italy) were blood typed. The prevalence of A, B and AB blood types in northern and southern cats were 91.0%, 5.2%, 3.8%, and 77.2%, 12.1% and 10.7%, respectively. The prevalence of type-A blood in southern cats was significantly lower (p = 0.0001) than in northern cats, while type-B and AB blood were significantly higher (p = 0.0085 and p = 0.0051, respectively) in Southern compared to Northern Italian cats. Alloantibodies against type-A blood were found in 94.1% of type-B cats, 11.2% of type-A cats had alloantibodies against type-B blood, while no type-AB cats had alloantibodies with no significant difference between the two Italian populations. Type-AB prevalence in non-pedigree cats in Southern Italy was the highest reported in Europe. Italian type-A cats had the lowest worldwide prevalence of alloantibodies against type-B blood. These results highlight the usefulness of regional studies to report different prevalences in feline blood types and reinforce the importance of blood typing cats before transfusions and mating.